The Realization of a Virtual Past in Günter Grass's Crabwalk - Paul A. Youngman (Studies in 20th & 21st Century Literature, 2008)
In his 1999 Nobel lecture, Günter Grass declares narration to be "a form of survival as well as a form of art." He sets out to demonstrate this declaration in his latest novella Crabwalk (2002), in which he echoes Walter Benjamin's concerns regarding war and information. The twist for Grass, the author who writes exclusively on his Olivetti typewriter, is that he analyzes the Internet as a narrative medium in his most recent work. This paper analyzes Crabwalk as a look at various forms of media—oral memories, historical monographs, film, and a website—through which humans narrate the past, in this case the 1945 sinking of the Wilhelm Gustloff, a German KdF (Strength Through Joy) ship, by a Russian U-boat. The last medium, the Internet, is the focus of this paper as it serves as the central means of narrative development, as well as the single medium that inextricably intertwines Grass's "historical reality," the sinking of the Gustloff, with his "fictional reality," the murder of a "virtual" Jew by an apparently "virtual" Neo-Nazi.
Keywords: Günter Grass; Crabwalk; information; media; internet; oral memories; past; time; film. Wilhelm Gustloff; jew; judaism; neo-nazi